“THE GREAT EIGHT” AS A COMPETENCY MODEL FOR TOUR GUIDES - Zhumbei, Marianna (Collection of scientific papers «ΛΌГOΣ», 2022)
Today the scientists claim that a real tourism expert has to be characterized by high professionalism, thorough knowledge, communicativeness, progressiveness, skilled performance and competitiveness in the labour market.